2022
DOI: 10.1002/nop2.1306
|View full text |Cite
|
Sign up to set email alerts
|

Employability, organizational commitment and person–organization fit among nurses in China: A correctional cross‐sectional research

Abstract: Aim: This study aimed to explore the effect of training on organizational commitment, the mediating effect of employability and the moderating role of person-organization fit.Design: A correctional cross-sectional research design was adopted for this study. Methods: A questionnaire-based survey of 859 nurses in a public hospital in Western China was conducted to identify their perceptions of training, employability, organizational commitment and person-organization fit. Hierarchical linear regression and condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 65 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…For example, a study by Yan et al found that nurses who felt a strong P-O fit were likelier to have a positive attitude toward their organization. 19 Another study by Jehanzeb and Naz et al found a positive correlation between P-O fit and organizational commitment among nurses. 13 , 14 The findings are consistent with Risman et al, who showed that a strong P-O fit can reduce role ambiguity and conflict.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…For example, a study by Yan et al found that nurses who felt a strong P-O fit were likelier to have a positive attitude toward their organization. 19 Another study by Jehanzeb and Naz et al found a positive correlation between P-O fit and organizational commitment among nurses. 13 , 14 The findings are consistent with Risman et al, who showed that a strong P-O fit can reduce role ambiguity and conflict.…”
Section: Discussionmentioning
confidence: 96%
“…Yan et al found that the P-O fit significantly influences job satisfaction. 19 The P-O fit is found to be a predictor of positive outcomes such as quality performance, service quality, creative behavior, and less absenteeism. 28 …”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 94%
See 3 more Smart Citations